A comparison between the effect of Oral Melatonin and Hydroxyzine for preventing preoperative Anxiety in Pediatric Patients undergoing Adenotonsillectomy: A randomized, double-blinded controlled study - Sarah Omar Mousa; Amany Khairy Abo El Hussien; Gehad Hanafy Abdalgaliel (SVU - International Journal of Medical Sciences)
Background: Induction of anesthesia is one of the most anxiety-provoking factors of preoperative anxiety in children. Melatonin is a safe drug used in the management of anxiety. Hydroxyzine is a first-generation antihistaminic that crosses the blood-brain barrier, causing sedation. Objectives: Our study aimed to estimate the effect of a single preoperative oral melatonin versus hydroxyzine to prevent preoperative pediatric anxiety in adenotonsillectomy children. Patients and methods: In a randomized, double-blinded, prospective study, 90 children of both sexes aged 3 to 10, were divided into three equal groups, all the patients received 10 ml of apple juice 2 hours preoperatively. In group M 0.1mg/kg of melatonin syrup was added, group H 1mg/kg of crushed hydroxyzine tablet was added, while group C received the juice alone. The primary outcome was the preoperative anxiety evaluated by the ease of parenteral separation scale, and the secondary outcomes were the compliance with the anesthesia induction mask assessed by the modified preoperative anxiety scale of Yale, the preoperative sedation evaluated by the Ramsay scale, and postoperative pain. Results: The hydroxyzine group showed the best cooperation during parenteral separation and the least anxiety (P =0.001), then melatonin (P =0.01) compared to the placebo. Pre-operative anxiety was measured before and during induction, hydroxyzine was better than melatonin and placebo. There were statistically insignificant differences between the study groups regarding preoperative sedation and postoperative pain. Conclusion: Hydroxyzine is more effective than melatonin and placebo for easiness of parenteral separation, reducing anxiety in the operative room, and increasing compliance with the mask in pediatric patients without causing sedation. Melatonin was superior to placebo.